COMPUTATIONS OF THE GROUND STATE ENERGIES PER ATOM FOR DIAMOND, FULLERENES AND GRAPHITE USING FHI-aims CODE (FUDMA JOURNAL OF SCIENCES, 2023)
In this work the total ground state energy per atom for Fullerenes (C60), Graphite and Diamond were computed using Density Functional Theory (DFT) code FHI-aims (Fritz Haber Institute- ab initio molecular simulations). The density functionals used are the local-density approximation (LDA) in the parameterization by Perdew and Wang 1992, Perdew and Zunger 1981, the generalized gradient functional PBE, and PBE+vdW approach as defined by Tkatchenko and Scheffler. The results obtained from the computations of the ground state energies of diamond, fullerenes and graphite were -1028.51549311 eV, -1027.194 eV and -1035.469 eV, respectively. These results agree with both experimental and theoretical results regardless of the exchange and correlation functionals used.
Keywords: Total Ground state Energy per Atom, DFT, FHI-aims, LDA, and GGA